Piecing me together - e uthor (New York : Bloomsbury, 2017)
Jade believes she must get out of her poor neighborhood if she's ever going to succeed. Her mother tells her to take advantage of every opportunity that comes her way. And Jade has: every day she rides the bus away from her friends and to the private school where she feels like an outsider, but where she has plenty of opportunities. But some opportunities she doesn't really welcome, like an invitation to join Women to Women, a mentorship program for "at-risk" girls. Just because her mentor is black and graduated from the same high school doesn't mean she understands where Jade is coming from. She's tired of being singled out as someone who needs help, someone people want to fix. Jade wants to speak, to create, to express her joys and sorrows, her pain and her hope. Maybe there are some things she could show other women about understanding the world and finding ways to be real, to make a difference.
680L
Coretta Scott King Author Award, 2018
Newbery Honor, 2018
School Library Journal's Best Books, 2017
Accelerated Reader
Keywords: Mentoring -- Juvenile fiction; Private schools -- Juvenile fiction; African American high school students -- Attitudes -- Juvenile fiction; African American girls -- Juvenile fiction; Mentoring -- Fiction; High schools -- Fiction; Schools -- Fiction; African Americans -- Fiction; JUVENILE FICTION -- Girls & Women; JUVENILE FICTION -- People & Places -- United States -- African American; JUVENILE FICTION -- Social Themes -- Adolescence